IMPLEMENTASI PADA PASIEN DENGAN PPOK DI RUANG EDELWEIS ATAS RSUD KARDINAH TEGAL - Nur Baety Sa’diyah; Made Suandika (LPPM Institut Pendidikan Nusantara Global, 2023)
COPD is a disorder that appears in the respiratory system where a person will experience difficulty breathing and this can be caused by many things. This study used a descriptive method where sample criteria were determined and for implementation in the Edelweiss Upper Room, Kardinah Hospital, Tegal City. From the results of scientific work, it was found that the conclusion from the evaluation of actions that have been carried out for 3x24 hours is a therapeutic measure of administering drugs as recommended by doctors such as injections of levofloxacin, ranitidine and 2 mg salbutamol tablets, monitoring fluid intake and output and monitoring oxygen in patients being checked periodically. During 3x24 hours data was obtained that the patient's condition was quite improved and stable.